PERBEDAAN MOTIVASI DAN KEPUASAN MENGIKUTI PRAKERIN BERDASARKAN BIDANG KEAHLIAN SERTA IMPLIKASINYA DALAM PENYUSUNAN PROGRAM BK KARIER - Sri Florina laurence zagoto (Jurnal Education and Development, 2018)
This research was motivated by the phenomena that occur in the Industrial Internship (Prakerin). This study was aimed to describe: (1) the motivation of students follow the Prakerin accordance of expertise and not accordance of expertise, (2) the satisfaction of students follow the Prakerin accordance of expertise and not accordance of expertise, (3) the differences motivation between of students follow the Prakerin accordance of expertise and not accordance of expertise, (4) the differences satisfaction between of students follow the Prakerin accordance of expertise and not accordance of expertise, and (5) the career guidance and counseling program of SMK Swasta Kristen BNKP Telukdalam in increasing motivation and satisfaction of students to follow Prakerin. This study used quantitative methode by using comparative descriptive and qualitative method. The population were 225 students of class XII SMK Swasta Kristen BNKP Telukdalam. Total sample were 176 students that selected by purposive sampling and informant qualitative approach is the counseling teacher. The instrument were scale of motivation and scale of satisfaction to follow Prakerin shaped questionnaire, while instruments in qualitative approach was researcher.Data were analyzed using test requirements of normality, test the hypothesis by using t-test, and analysis of interview results. The results of the research indicate that: (1) the motivation of students followed the Prakerin accordance of expertise is in very high category, while the motivation of students followed the Prakerin not accordance of expertise is in low category, (2) the satisfaction of students followed the Prakerin accordance of expertise is in very high category, while the satisfaction of students followed the Prakerin not accordance of expertise is in low category, (3) there is a difference between motivation of students followed the Prakerin accordance of expertise and not accordance of expertise, (4) there is a difference satisfaction of students followed the Prakerin accordance of expertise and not accordance of expertise, and (5) the career guidance and counseling program of SMK Swasta Kristen BNKP Telukdalam did not go well, so need the cooperation of various parties to formulate and develop programs to improve motivation and satisfaction follow the Prakerin.